Elements of the exercise of popular revolutionary violence and the improvement of torture as a practice of state political repression in Chile (1964-1973) - Calderón Opazo René Fernando (Латиноамериканский исторический альманах)
This paper seeks to investigate the process of political radicalization and the exercise of popular revolutionary violence, and the corresponding improvement of torture as a practice of state political repression in Chile, in the period prior to the coup d'état of September 11, 1973. For these purposes, the repressive practice of torture in the period 1964-1973, exercised by the state against those defined as political enemies by the governments of the time, in correlative response to the radicalization of direct actions in which they used revolution-ary violence in the public space, will be addressed. There is evidence of an escalation of revolutionary violence, with the appearance of different types of armed actions, which were unknown during the Frei Montalva government (1964-1970) and reached their peak during the Allende presidency (1970-1973) with the outbreak of the only suicide bombing in Chilean history. In direct correlation, the methods of torture worsened with the appearance, under the Frei government, of the use of drugs, the breaking of bones and the introduction of Brazilian hanging techniques, and during the Allende presidency with the application of torture to pregnant women, resulting in the death of the fetus.